Analysis on fabrication of micro-tools by micro-electrochemical machining process. (1st January 2013) - Das, Alok Kumar; Saha, Partha
In pulse micro-electrochemical machining process, material dissolution takes place at very close vicinity of tool electrode due to localisation of electric field and hence this process can be utilised potentially for the fabrication of micro components with high dimensional accuracy. In the present context, experiments are carried out with an indigenously developed set up to fabricate micro-electrodes (tools) of diameter < 30 μm from cylindrical copper bars of initial diameter 780 μm. The influence of different experimental parameters on material dissolution rate during the fabrication of micro electrodes has been investigated. It is observed that with increase in pulse-on-time, frequency of pulse power supply and applied voltage, the material removal rate increases; but with the increase in concentration of electrolyte material removal rate decreases as the mobility of ions decreases. The detailed analysis of the experimental results is described in this paper.